Pengaruh Harga dalam Meningkatkan Jumlah Konsumen pada Produksi Aksesoris JIP di H&Jee Bumper Ditinjau Berdasarkan Perspektif Ekonomi Syari’ah - Maula, Inayatul; Salsabila, Yusro Khalda (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2025)
Pricing is a critical element in business strategy, significantly influencing a company's financial performance, customer perception, and brand positioning. Poor pricing decisions can result in long-term negative impacts, including loss of competitiveness and consumer trust. In Islamic economic principles, price functions as a fair standard of exchange between goods or services and money, requiring mutual consent between buyer and seller. While various pricing methods may be employed, they must adhere to Islamic ethical standards emphasizing justice, transparency, and the prohibition of exploitation. In modern markets, factors such as deregulation, economic shifts, and intense competition increase the complexity of pricing strategies. Price often serves as a signal of product quality, especially when consumers face difficulty assessing a product’s value. Mispricing, particularly when unethical or externally imposed, can trigger public dissatisfaction. For example, government-determined fuel prices have, in some cases, led to social unrest and protest. This paper aims to explore pricing not only as a strategic business tool but also through the lens of Islamic economic thought, highlighting the balance between market forces and ethical considerations.